X-ray, optical and dielectric studies of diffused phase transitions in NaNbO3-based solid solution crystals - Raevskaya, S; Semenchev, A; Abdulvakhidov, K; Raevski, I; Prosandeev, SA; Shilkina, L; Smotrakov, V; Eremkin, V; Shuvaeva, V; Glazer, A (2004)
In flux-grown (1-x)NaNbO3 -(x)Gd1/3NbO3 solid solution crystals a diffusion of the dielectric permittivity epsilon maximum grows with x and increases dramatically when x exceeds a threshold value x 0 approximate to 0.1. Optical studies by the rotating-polarizer method show that Gd-doping results in a very small mean size of twins and the distribution of the birefringence image becomes very messy. In the x < x(0) range the changes of lattice parameters and birefringence corresponding to the epsilon(T) anomaly were revealed. The results obtained are in line with the assumption that phase transition diffusion in NaNbO3 is a result of the local strains stemmed from the impurities.